The Influence of Job Descriptions and Job Placements on the Work Performance of Educational Personnel of Indragiri Islamic University - M. Ramli; Edi Susanto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This study aims to obtain information about the relationship between free   Job Description, Job Placement,        Job Performance.   variables, job descriptions (X1) and job placements (X2), with bound variables, the work performance of educational personnel (Y), at Indragiri Islamic University, both singly and collectively. The population of this study is the entire educational staff at Indragiri Islamic University which amounts to 76 people. Data collection was carried out using the survey method through a questionnaire filled out by respondents. Then the data is analyzed using multiple regression analysis through the SPSS program. From the results of the analysis, the regression equation was obtained: Y = 14,924 + 0.381X1 + 0.281X2, it can be concluded that job descriptions (X1) have an effect of 38.1% and job placements (X2) have an effect of 28.1%. Meanwhile, the relationship between dependent and independent variables, namely job description (X1) and job placement (X2) with dependent variables, namely the performance of educational personnel (Y) has a correlation index of 78.0%, meaning that the relationship is very strong. Together, the job description variable (X1) and the job placement variable (X2) had a significant effect on the educational personnel performance variable (Y) with a determination index value of 56.3%, while the remaining 43.7%, influenced by other variables that were not studied in this study.